2020
DOI: 10.1101/2020.05.05.20091934
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Screening of SARS-CoV-2 among homeless people, asylum-seekers and other people living in precarious conditions in Marseille, France, March–April 2020

Abstract: 150/150 words)Surveillance of SARS-CoV-2 infection among sheltered homeless and other vulnerable people might provide the information needed to prevent its spread within accommodation centres. In March-April, we enrolled 411 homeless individuals, 77 asylum-seekers, 58 people living in precarious conditions, and 152 employees working in these accommodation centres and collected nasal samples. SARS-CoV-2 carriage was assessed by quantitative PCR. Overall, 49 (7.0%) people were positive for SARS-CoV-2, including … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Overall, 22 unique cohorts of participants described in 24 studies (15 cohorts, 7 cross sectional) reported the proportion of asymptomatic infection at initial testing and/or the proportion of COVID-19 infections remaining asymptomatic throughout follow-up; study characteristics are summarized in Table 1 . Study cohorts were from the USA (n = 10) [ 6 , 9 , 60 62 , 66 , 69 , 73 , 75 , 78 , 80 , 81 ], Europe (n = 8) [ 63 , 67 , 68 , 70 , 72 , 74 , 76 , 77 ], and Asia (n = 4) [ 65 , 70 , 79 , 84 ]. Definition of asymptomatic infection was variable among studies, ranging from absence of symptoms in the previous 14 days to only absence of symptoms at time of testing.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 22 unique cohorts of participants described in 24 studies (15 cohorts, 7 cross sectional) reported the proportion of asymptomatic infection at initial testing and/or the proportion of COVID-19 infections remaining asymptomatic throughout follow-up; study characteristics are summarized in Table 1 . Study cohorts were from the USA (n = 10) [ 6 , 9 , 60 62 , 66 , 69 , 73 , 75 , 78 , 80 , 81 ], Europe (n = 8) [ 63 , 67 , 68 , 70 , 72 , 74 , 76 , 77 ], and Asia (n = 4) [ 65 , 70 , 79 , 84 ]. Definition of asymptomatic infection was variable among studies, ranging from absence of symptoms in the previous 14 days to only absence of symptoms at time of testing.…”
Section: Resultsmentioning
confidence: 99%
“…Eight of the cross-sectional quantitative studies were conducted in the USA [18][19][20][21][22][23][24][25] , one in Canada 26 and one in France 27 . All studies collected data from March to early May 2020 during the first wave of the SARS-Cov-2 pandemic, except one 20 , conducted from April to August 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Nine articles reported PCR-based estimates of SARS-Cov-2 prevalence (with some offering additional data on other health or living conditions of homeless people), while one study 24 researched shelter tenants' knowledge and perception of COVID-19 and their adherence to behavioural rules. A total of six articles reported prevalence estimates for staff working at the homeless facilities 18,[21][22][23]26,27 . Studies' characteristics are presented in Table 1 Prevalence of SARS-Cov2 in homeless shelters…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations